2006
DOI: 10.1073/pnas.0600930103
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides provide neuroprotection against ischemic stroke: Discovery by a brain slice-based compound screening platform

Abstract: We report here the results of a chemical genetic screen using small molecules with known pharmacologies coupled with a cortical brain slice-based model for ischemic stroke. We identified a smallmolecule compound not previously appreciated to have neuroprotective action in ischemic stroke, the cardiac glycoside neriifolin, and demonstrated that its properties in the brain slice assay included delayed therapeutic potential exceeding 6 h. Neriifolin is structurally related to the digitalis class of cardiac glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 47 publications
11
77
0
2
Order By: Relevance
“…We saw no effect of NXY-059 on tyrosine nitration at concentrations well above the maximal concentration of 200 mmol/L used by Maples et al (2001). A recent paper (Wang et al, 2006) did claim that low concentrations of NXY-059 were cytoprotective in a brain slice preparation, but the nitrone studied was in fact PBN (DC Lo, personal communication). Our study is therefore the first test for a cytoprotective effect of NXY-059 on neuronal-type cells in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…We saw no effect of NXY-059 on tyrosine nitration at concentrations well above the maximal concentration of 200 mmol/L used by Maples et al (2001). A recent paper (Wang et al, 2006) did claim that low concentrations of NXY-059 were cytoprotective in a brain slice preparation, but the nitrone studied was in fact PBN (DC Lo, personal communication). Our study is therefore the first test for a cytoprotective effect of NXY-059 on neuronal-type cells in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…Recently several compounds showing inhibitory potency on Na + ,K + -ATPase, such as cardiac glycosides, ginsenosides, and magnesium lithospermate B (the major water soluble ingredient in the dried roots of medicinal plant Salvia miltiorrhiza), were demonstrated to provide neuroprotection against ischemic stroke in a cortical brain slicebased compound screening platform [6,37,38] . Similarly, oleanolic acid, showing inhibitory potency on Na + ,K + -ATPase in this study, has also been demonstrated to display neuroprotective effect against focal cerebral ischemic injury [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Though these small-molecules can reverse phenotypes of several complex neurodegenerative disorders in cell culture and some invertebrate animal models, prioritization and testing in more validated mouse models is a serious challenge. More complex HCS assay and testing in primary cell culture models or invertebrate animal models can provide a reasonable means to prioritize these hits [54,58,64]. However, activity in a small range of secondary assays, though useful for prioritizing such active compounds, is by no means a proof that inactive compounds do not merit further study.…”
Section: Hts Achievementsmentioning
confidence: 99%
“…We have recently described a HCS screen for ischemic stroke based on the creation of a "sentinel" population of pyramidal neurons in cortical brain slice explants via biolistic transfection of Green Fluorescent Protein [58]. Subsequent to oxygen-glucose deprivation (OGD), these GFP-expressing sentinel neurons provide a living index of the extent and time course of the ischemic damage produced.…”
Section: High Content Screens (Hcs)mentioning
confidence: 99%